Structured P2P Overlay of Mobile Brokers for Realizing Publish/Subscribe Communication in VANET - Tulika Pandey; Deepak Garg; Manoj Madhava Gore (The Scientific World Journal)
Publish/subscribe communication paradigm provides asynchrony and decoupling, making it an elegant alternative for designing applications in distributed and dynamic environment such as vehicular ad hoc networks (VANETs). In this paradigm, the broker is the most important component that decouples other two components, namely, publisher and subscriber. Previous research efforts have either utilized the deployment of distributed brokers on stationary road side info-stations or have assigned the role of broker to any moving vehicle on ad hoc basis. In one approach, lots of preinstalled infrastructures are needed whereas, in another, the quality of service is not guaranteed due to unpredictable moving and stopping patterns of vehicles. In this paper, we present the architecture of distributed mobile brokers which are dynamically reconfigurable in the form of structured P2P overlay and act as rendezvous points for matching publications and subscriptions. We have taken city buses in urban settings to act as mobile brokers whereas other vehicles are considered to be in role of publishers and subscribers. These mobile brokers also assist in locating a vehicle for successful and timely transfer of notifications. We have performed an extensive simulation study to compare our approach with previously proposed approaches. Simulation results establish the applicability of our approach.